A contrastive analysis of linguistic and socio-cultural features of words denoting “male” characteristics In english and vietnamese - Phạm Thị Ánh Hằng (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2025)
Learning Vocabulary is one of the most important parts in learning English, vocabulary is taught at high school through all four skills Reading, Speaking, Listening, Writing and Language focus. Because students’ mistakes in using vocabulary are unavoidable, understanding the usage of the word is thought to be one of important part that helps students make progress in their learning. Moreover, translation process will be a big challenge for those who are lack of vocabulary or for those who don’t have deep understanding on the usage of words. For that reason, learners should be provided with the basic knowledge of the meanings and the usage of the words so that students can improve their learning English. More importantly, they would know how to use these words in real communication. Studying all the words at the same time is impossible. So the objectives of the study are to investigate the linguistic and socialcultural features of words denoting male characteristics only. In order to conduct this research, experiential meaning in Functional Grammar has been used as a theoretical base to classify words denoting male characteristics into specific categories. In addition, a collection of words denoting male characteristics taken from various sources in English and in Vietnamese has been used as the effective device. Via this analysis, the study aims at presenting some commonly used English words denoting male characteristics. Also, a contrastive analysis of the linguistics and social cultural features of words denoting male characteristics in English and Vietnamese will be conducted to find out the similarities and differences between the two languages. Besides, this paper may help Vietnamese learners to use words appropriately and to understand language in cross-cultural communication. Finally, the implications in teaching, learning, and translating the English language are dealt with.